La gouvernance de la vie nocturne au prisme du territoire : une approche exploratoire des conseils de la nuit à Paris et à Nantes - Michael Spanu; Yacine Mokhnachi (Bollettino della Società Geografica Italiana, 2019)
Nightlife challenges the development and organization of urban spaces and requires new modes of regulation. Simultaneously, the notion of governance helps understand the evolution of public policies in regard to locality, horizontality and participation. The combination of nightlife and governance reshapes the traditional geography of public policies regarding night time, as attested by the fact that several models of nightlife governance are currently being tested across Europe. In this article, we focus on two nightlife governance models, in Nantes and Paris. Results show that both cases articulate transversality and a certain degree of local actors participation, within a political frame marked by republicanism where territorial inclusion/structuration and the performance of the public sector’s legitimity are constantly negotiated.